Developing Countries' Changing Participation in World Trade - Martin, Will (World Bank, 2013)
Recent year have seen substantial reductions in trade policy and other barriers inhibiting developing country participation in world trade. Lower barriers have contributed to a dramatic shift in the pattern of developing country trade-away from dependence on commodity exports to much greater reliance on manufacture and services. In addition, exports to other developing countries have become much more important. These changes have profound implications for the role played by developing countered in the world economy and trade system.